STUDY ON DEGRADATION OF SILK FIBROIN BY IRRADIATION TREATMENT FOR COSMETIC AND PHARMACEUTICAL APPLICATIONS - TRAN , BANG DIEP; TRAN , MINH QUYNH; HOANG , DANG SANG; PHAM , QUANG HIEU; HOANG , PHUONG THAO; NGUYEN , VAN BINH; PHAM , DUY DUONG; NGUYEN , THUY HUONG TRANG (Nuclear Science and Technology, 2012)
As a kind of protein, silk fibroin is created with silkworm Bombyx mori in products of silk. The fibroin was irradiated using Co-60 gamma source and its degradability and solubility were investigated with various radiation doses to apply in pharmacy and cosmetic. Addition to the morphological changes of irradiated fibroin fibers shows that its mechanical properties were much influenced by the irradiation. Tensile strength and elongation at break of the silk fibroin significantly decreased with increasing of radiation dose up to 1000kGy. The tensile strength and elongation at break of the irradiated fibroin at 1000kGy reduced to 71% and 94% respectively in compared with non-irradiated one. The solubility of silk fibroin in both calcium chloride (CaCl2/C2H5OH/H2O=1:2:8) in mole ratio and distilled water were improved by the irradiation. UV spectrometry revealed the structure of silk fibroin was also changed by irradiation.